2019
DOI: 10.1007/s10579-018-09442-4
|View full text |Cite
|
Sign up to set email alerts
|

Vector space explorations of literary language

Abstract: Literary novels are said to distinguish themselves from other novels through conventions associated with literariness. We investigate the task of predicting the literariness of novels as perceived by readers, based on a large reader survey of contemporary Dutch novels. Previous research showed that ratings of literariness are predictable from texts to a substantial extent using machine learning, suggesting that it may be possible to explain the consensus among readers on which novels are literary as a consensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Topic modeling is a method used to analyze the content of texts by revealing hidden topics of documents in a collection. It has been used in computational studies of literary texts before, though with different objectives and background assumptions (van Cranenburgh et al, 2019 ). We are interested in the changes of topic distributions along a text, as it can be expected to have an impact on how “a reader progresses through a text with a growing understanding for its content, topics and themes” (Wallot et al, 2014 , p. 1749).…”
Section: Measurable Properties Of Textmentioning
confidence: 99%
See 3 more Smart Citations
“…Topic modeling is a method used to analyze the content of texts by revealing hidden topics of documents in a collection. It has been used in computational studies of literary texts before, though with different objectives and background assumptions (van Cranenburgh et al, 2019 ). We are interested in the changes of topic distributions along a text, as it can be expected to have an impact on how “a reader progresses through a text with a growing understanding for its content, topics and themes” (Wallot et al, 2014 , p. 1749).…”
Section: Measurable Properties Of Textmentioning
confidence: 99%
“…van Cranenburgh and Bod ( 2017 ) used frequency distributions of lexical and syntactic features to model human ratings of texts as more or less “literary” (see also Ashok et al, 2013 ; van Cranenburgh and Koolen, 2015 for similar approaches). In van Cranenburgh et al ( 2019 ), summary statistics derived from topic modeling (Latent Dirichlet Allocation) and paragraph vectors are used to predict degrees of “literariness.” Maharjan et al ( 2017 ) explore a wide variety of features (including “readability”) that can be used to classify texts in terms of “likability.” Other standard methods of computational linguistics used in this context include sentiment and emotion analysis (Alm and Sproat, 2005 ; Francisco and Gervás, 2006 ; Kakkonen and Galić Kakkonen, 2011 ; Mohammad, 2011 ; Reagan et al, 2016 ; Maharjan et al, 2018 ). Global statistical properties such as complexity and entropy have been used to study the regularity (Mehri and Lashkari, 2016 ; Hernández-Gómez et al, 2017 ) and the quality of texts (Febres and Jaffe, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of the update of machine learning in industry, Chiticariu et al [6] noted a gap in the volume of academic research on machine learning, compared with lower levels of uptake within industry and found the causes of this pertained to training data, interpretability and incorporation of domain knowledge. Similarly, the relatively low uptake of machine learning methods in the digital humanities has been attributed to issues pertaining to interpretation and trust [34,13,15]. Imparting domain knowledge into the process of text analysis through interpretation and annotation is also central to humanities research [17,37].…”
Section: Text Mining In the Humanitiesmentioning
confidence: 99%